2011
DOI: 10.1002/hbm.21247
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral lateralization of praxis in right‐ and left‐handedness: Same pattern, different strength

Abstract: We aimed to investigate the effect of hand effector and handedness on the cerebral lateralization of pantomiming learned movements. Fourteen right-handed and 14 left-handed volunteers performed unimanual and bimanual tool-use pantomimes with their dominant or nondominant hand during fMRI. A left hemispheric lateralization was observed in the right- and left-handed group regardless of which hand(s) performed the task. Asymmetry was most marked in the dorsolateral prefrontal cortex (DLPFC), premotor cortex (PMC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
1
2

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 83 publications
12
68
1
2
Order By: Relevance
“…In particular, we noticed a significant involvement of the left relative to the right hemisphere, underlining that its higher-order control processes are required for an efficient motor performance [37,45,46]. This lateralisation profile was independent of hand dominance, which is in agreement with previous observations from tool-use and bimanual actions [23,26,47,56]. It implies that both hemispheres do not contribute equally to cognitive-motor processes, and is in line with work that has shown that patients with left-sided brain damage demonstrate deficits of the planning and execution of heterogeneous sequences, whereas impairment of repetitive sequences is more subtle [18].…”
Section: Functional Connectivity Patterns and Implications For Goal-dsupporting
confidence: 91%
“…In particular, we noticed a significant involvement of the left relative to the right hemisphere, underlining that its higher-order control processes are required for an efficient motor performance [37,45,46]. This lateralisation profile was independent of hand dominance, which is in agreement with previous observations from tool-use and bimanual actions [23,26,47,56]. It implies that both hemispheres do not contribute equally to cognitive-motor processes, and is in line with work that has shown that patients with left-sided brain damage demonstrate deficits of the planning and execution of heterogeneous sequences, whereas impairment of repetitive sequences is more subtle [18].…”
Section: Functional Connectivity Patterns and Implications For Goal-dsupporting
confidence: 91%
“…18,40 In our study, no significant difference in handgrip strength had been found between the dominant and non-dominant hands in left-handed students. A result, which had been revealed by others 41,42 This can be attributed to that most tools and appliances in daily living are designed for the right hand. Therefore, the left-handed people are compelled to use their non-dominant hands for many daily activities.…”
mentioning
confidence: 89%
“…We need to point out of course that EEG records electrical activity at the surface of the head and any claims regarding the brain sources of the ERPs should be treated with great caution. Keeping this in mind, it is worth mentioning that the left premotor cortex is considered to be part of a larger network that supports the production of object-directed movements (Vingerhoets et al, 2012) and that it is associated with the prediction and organization of effector-independent complex action sequences (Stadler, Schubotz, von Cramon, Springer,& Prinz, 2011;Haaland, Elsinger,Mayer,Durgerian, & Rao, 2004). Thus, it is conceivable that the enlarged CNV during joint action planning may reflect the implicit representation of the partnerʼs upcoming action and the organization of the two individual actions into a complex joint task.…”
Section: Action Representationmentioning
confidence: 99%